2012
DOI: 10.1175/jcli-d-11-00553.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Inconsistent Relationship between Pacific and Atlantic Niños*

Abstract: The tropical Atlantic wind response to El Niñ o forcing is robust, with weakened northeast trade winds north of the equator and strengthened southeast trade winds along and south of the equator. However, the relationship between sea surface temperature (SST) anomalies in the eastern equatorial Pacific and Atlantic is inconsistent, with El Niñ o events followed sometimes by warm and other times by cold boreal summer anomalies in the Atlantic cold tongue region. Using observational data and a hindcast simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 34 publications
(34 reference statements)
4
88
3
1
Order By: Relevance
“…As a result, although no SST restoring is used, SST is implicitly damped toward the prescribed surface air temperatures and thus ceases to be a fully prognostic variable. L€ ubbecke and McPhaden (2012) showed that the model simulation successfully captures the interannual variability in the eastern equatorial Atlantic and Pacific. Observed and simulated time series of SST and SSH anomalies are highly correlated and agree in amplitude.…”
Section: Methodsmentioning
confidence: 94%
“…As a result, although no SST restoring is used, SST is implicitly damped toward the prescribed surface air temperatures and thus ceases to be a fully prognostic variable. L€ ubbecke and McPhaden (2012) showed that the model simulation successfully captures the interannual variability in the eastern equatorial Atlantic and Pacific. Observed and simulated time series of SST and SSH anomalies are highly correlated and agree in amplitude.…”
Section: Methodsmentioning
confidence: 94%
“…Keenlyside and Latif 2007;Burls et al 2011;Lübbecke and McPhaden 2012;Richter et al 2013). Obvious are the differences in timing characteristics: Both positive and negative ENSO events generally peak in boreal winter and last for several months and in some cases even longer than a year.…”
Section: Introductionmentioning
confidence: 99%
“…El Niño events, for example, are known to mediate anomalous warming in the northern tropical Atlantic through a corresponding weakening of the trade winds (Enfield and Mayer 1997;Sutton et al 2000;Alexander et al 2002;Chang et al 2006). The connection with the southern equatorial Atlantic (i.e., the Atlantic Niño domain), however, is far less clear, with El Niño events sometimes followed by warm anomalies, and other times by cold (Huang 2004;Chang et al 2006;Lübbecke and McPhaden 2012). This inconsistency has been interpreted in terms of competing dynamical and thermodynamical processes (Chang et al 2006) and a delayed negative SST feedback (Lübbecke and McPhaden 2012).…”
Section: Introductionmentioning
confidence: 99%